2016
DOI: 10.3904/kjim.2015.291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraductal ultrasonography-directed and cholangiography-directed endoscopic retrograde biliary drainage in patients with a biliary obstruction

Abstract: Background/Aims:Endoscopic retrograde biliary drainage (ERBD) has become a standard procedure in patients with a biliary obstruction. Intraductal ultrasonography (IDUS) has emerged as a new tool for managing extrahepatic biliary diseases. IDUS-directed ERBD can be performed without conventional cholangiography (CC). The goal of this study was to assess the effectiveness and safety of IDUS-directed ERBD compared to CC-directed ERBD in patients with an extrahepatic biliary obstruction.Methods:A total of 210 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Because of the bile component in the bile duct as a medium, ultrasound has good conductivity. So far, several studies have reported on IDUS for the diagnosis of CBD stones ( 16 , 17 ). For example, Kim et al ( 18 ) found that IDUS is useful for detecting occult CBD stone on ERCP in icteric patients with highly suspected CBD stones.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the bile component in the bile duct as a medium, ultrasound has good conductivity. So far, several studies have reported on IDUS for the diagnosis of CBD stones ( 16 , 17 ). For example, Kim et al ( 18 ) found that IDUS is useful for detecting occult CBD stone on ERCP in icteric patients with highly suspected CBD stones.…”
Section: Discussionmentioning
confidence: 99%